2001
DOI: 10.1161/hy09t1.094005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Vitamins C and E Are Associated With Altered Activation of Vascular NADPH Oxidase and Superoxide Dismutase in Stroke-Prone SHR

Abstract: Abstract-Ascorbic acid (vitamin C) and ␣-tocopherol (vitamin E) have antioxidant properties that could improve redox-sensitive vascular changes associated with hypertension. We determined whether vitamins C and E influence vascular function and structure in hypertension by modulating activity of NADPH oxidase and superoxide dismutase (SOD). Adult stroke-prone spontaneously hypertensive rats (SHRSP) were divided into 3 groups: control (C; nϭ6), vitamin C-treated (vit C, 1000 mg/day; nϭ7), and vitamin E-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
277
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(295 citation statements)
references
References 53 publications
(50 reference statements)
15
277
0
3
Order By: Relevance
“…In order to further support a role for oxidative stress in experimental hypertension, treatment of hypertensive rats or mice with antioxidant vitamins, SOD mimetics (tempol [4-hydroxy-2,2,6,6-tetramethyl piperidinoxyl]), free radical scavengers, or tetrahydrobiopterin (BH4) attenuate or prevent development of hypertension and its associated target organ damage (37,72).…”
Section: And Through the Dysegulation Of T-regulatory And T-effector mentioning
confidence: 99%
“…In order to further support a role for oxidative stress in experimental hypertension, treatment of hypertensive rats or mice with antioxidant vitamins, SOD mimetics (tempol [4-hydroxy-2,2,6,6-tetramethyl piperidinoxyl]), free radical scavengers, or tetrahydrobiopterin (BH4) attenuate or prevent development of hypertension and its associated target organ damage (37,72).…”
Section: And Through the Dysegulation Of T-regulatory And T-effector mentioning
confidence: 99%
“…12,16 It was also shown that vitamin C inhibited activation of mitogen-activated protein kinase and VSMC proliferation in cultured rat aortic smooth muscle cells, 26 and in an in vivo experiment it was demonstrated that vitamin C supplementation decreased activation of NADPH oxidase and superoxide anion generation, prevented vascular hypertrophy and increased plasma total antioxidant status and superoxide dismutase in arterial wall in stroke-prone spontaneously hypertensive rats. 30 Vitamin C also abolished ET-1-induced increased interleukin-6 release in humans. 28 Taken together, these data and our findings suggest that arterial wall hypertrophy is a redoxsensitive process and that plasma antioxidants may prevent the deleterious effect of the ET-1-induced pathway leading to IMT and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…The vascular effect of antioxidants has been observed in vitro and in animal models of atherosclerosis (Chen et al, 2001;Wu et al, 2006). However, data on long-term vascular impact of antioxidant supplementation in humans are limited and controversial.…”
Section: Discussionmentioning
confidence: 99%